(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In article the analyses of scientifi c-theoretical concepts of international economical relations in political science. It should be noted international closely related substantiated with international political relations that refer to sphere of state interests and intergovernmental relations and also the sphere of authority relations on international level. In its complexity it aimed at resolving the problems of surviving and human society development, elaboration of mechanisms of consent interests of various world politics subjects and development of equal relations between them, preventing of global and regional confl icts, creating of stable and fair world order.